Non-invasive Analysis of Progesterone Metabolites in Lactobacillus acidophilus and Saccharomyces cerevisiae Supplemented Endangered Asian Elephants: - Chharang, Dharmendra; Choudhary, Sheela; Kumar, Vinod; Umapathy, G. (Indian Journal of Animal Nutrition, 2023)
Non-invasive analysis has become a legitimate choice in wildlife biology, monitoring and global ecological research. The development of non-invasive progesterone hormone assays facilitates the conservation and management of wild animals as the population of wildlife, especially endangered Asian elephants, is being declined in their innate habitat. The role of live microbial cultures in endocrinology has also been stated and gut microbiota was shown to affect the production of steroid hormones in the gut. This research was carried out to assess the impact of the supplementation of probiotics on faecal progesterone metabolite concentrations in 18 female Asian elephants. They were randomly divided into three groups with six elephants in each. Experimental probiotics Lactobacillus acidophilus and Saccharomyces cerevisiae were administered @ 1 gm 1 × 109 CFU / 50 kg body weight per day orally to all the elephants of LACTO (T2) and SAC (T3) groups, respectively, whereas the CONT (T1) group received no probiotic. Faecal samples were taken on the 0, 30th, 40th and 50th day of the research. In conclusion, the supplementation of probiotics did not exhibit any significant difference in faecal progesterone metabolite concentrations in the different groups.